The Effect Of Some Plants Extracts On The Growth Of Streptococcus Pyogenes - Al-Athary, Ishtar Adnan (The Iraqi Journal of Veterinary Medicine, 2011)
In this study were choice some medical plants ( Matricaria chamomilla , Nigella sativa and Allium sativum ) and inhibitory their effect on Streptococcus pyogenes was tested ,which cause for many diseases especially respiratory disease andBecause of their availability and low cost of obtaining them ,study aimed to study the effect of extracts of these plants in growth of these bacteria isolated from aperson infected with tonsillitis. There was variation in bio effects of extracts among the species tested. The study show the presence effects of medical plants on growth of Streptococcus pyogenes is equal to the effect of both Matricaria chamomilla and Allium sativum and reached a concentration of 100 Mcg/ Dis , and the less effect with Nigella sativa concentration of 1000 Mcg/ Dis .